A 2, 5-difluoro benzene-based low cost and efficient polymer donor for non-fullerene solar cells. (1st September 2020) - Kini, Gururaj P.; Park, Hee Seon; Jeon, Sung Jae; Han, Yong Woon; Moon, Doo Kyung
Graphical abstract: Highlights: A new WBG polymer donor, PBDT-2FBnT, based on alternative BDT-based donor and 2, 5-difluoro benzene as the acceptor unit was successfully synthesized. PBDT-2FBnT processes highly coplanar geometry, and deep HOMO energy level of −5.48 eV. Non-fullerene organic solar cells fabricated with PBDT-2FBnT:ITIC (1:1, w/w) demonstrated remarkable PCE of 9.5% under thermal annealing. This study will encourage the explorations of easily scalable molecular designs that have tremendous potentials in commercial applications. Abstract: Although the latest progress in the power conversion efficiency (PCE) of non-fullerene polymer solar cells (NF-PSCs) has proved their potential as next-generation solar technologies, the development of efficient wide-bandgap (WBG) donor polymers having a low-cost and easily scalable molecular design is still lagging in terms of number and diversity. In this contribution, we report a new WBG polymer donor, PBDT-2FBnT, based on alternative benzodithiophene as the donor unit and 2, 5-difluoro benzene (2FBn) as the acceptor unit, which was prepared by a facile three-step process with an overall yield over 80% using cheap raw materials. Benefitting from the incorporation of an electron-deficient 2FBn unit, PBDT-2FBnT demonstrated lower frontier energy levels with an optical bandgap of 2.12 eV. Additionally, the combination of 2FBn with an adjacent two thiophene bridge in the polymer backbone significantly minimized the steric hindrance via non-covalent F···S and CH···F inter/intramolecular interactions, thereby promoting highly coplanar geometry for effective molecular packing and charge transport. Consequently, optimized blends of PBDT-2FBnT with an ITIC acceptor delivered complementary panchromatic absorption, well-aligned energy levels, higher charge carrier mobilities, and well-distributed nano-fibrillar morphology, thereby leading to a remarkable efficiency of 9.5% with a good trade-off between corresponding photovoltaic parameters. Thus, the high photovoltaic performance of PBDT-2FBnT together with simple preparation can provide a promising way for the future development of low-cost PSCs, and we can foresee further PCE improvements of the PBDT-2FBnT structure via synergistic variation of donor and acceptor material.